2004
DOI: 10.1101/gad.1229504
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis COP10 forms a complex with DDB1 and DET1 in vivo and enhances the activity of ubiquitin conjugating enzymes

Abstract: COP10 is a ubiquitin-conjugating enzyme variant (UEV), which is thought to act together with COP1, DET1, and the COP9 signalosome (CSN) in Arabidopsis to repress photomorphogenesis. Here, we demonstrate that COP10 interacts with ubiquitin-conjugating enzymes (E2s) in vivo, and can enhance their activity in vitro, an activity distinct from previous characterized UEVs such as MMS2 and UEV1. Furthermore, we show that COP10 forms a complex with UV-damaged DNA-binding protein 1a (DDB1a) and de-etiolated 1 (DET1), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
240
4
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(263 citation statements)
references
References 42 publications
18
240
4
1
Order By: Relevance
“…COP1 was shown to be modulated by light-activated photoreceptors, the COP9 signalosome, and the CDD complex (Saijo et al, 2003;Yanagawa et al, 2004;Chen et al, 2006;Yang and Wang, 2006). In this study, we showed that not only SPA1 but all four SPA Protein gel blot analysis showing the effects of cop1-6, cop9-1, cop10-1, and det1-1 mutations on the accumulation of COP1 and SPA proteins.…”
Section: Spa Proteins Are Critical For the Activity Of Cop1 In Vivomentioning
confidence: 68%
See 1 more Smart Citation
“…COP1 was shown to be modulated by light-activated photoreceptors, the COP9 signalosome, and the CDD complex (Saijo et al, 2003;Yanagawa et al, 2004;Chen et al, 2006;Yang and Wang, 2006). In this study, we showed that not only SPA1 but all four SPA Protein gel blot analysis showing the effects of cop1-6, cop9-1, cop10-1, and det1-1 mutations on the accumulation of COP1 and SPA proteins.…”
Section: Spa Proteins Are Critical For the Activity Of Cop1 In Vivomentioning
confidence: 68%
“…Biochemically, these COP/DET/FUS proteins belong to three groups of protein complexes: the COP1 complex(es), the COP9 signalosome (CSN), and the CDD complex (COP10, DDB1, and DET1). It has been hypothesized that all three complexes function collectively in the ubiquitination/proteasomemediated degradation of key photomorphogenesis-promoting transcription factors, thus achieving their repression of photomorphogenesis (Yanagawa et al, 2004;Chen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In Arabidopsis, the E3 ubiquitin ligase activity of the COP1 complex was recently proposed to be supported by direct interaction with the COP9 signalosome and the CDD (for COP10, DDB1, DET1) complexes (Yanagawa et al, 2004). These three complexes are defined by the COP/DET/FUS group of genes that share the cop phenotypes when mutated (e.g., Hoecker, 2005;.…”
Section: Introductionmentioning
confidence: 99%
“…Besides SCF TIR1/AFB1-3 , CUL1-type E3s have been implicated in the degradation of DELLA regulators in response to the phytohormone GA [SCF SLEEPY(SLY1) ; Dill et al, 2004] and the cell cycle inhibitor KIP1-RELATED PROTEIN1 (KRP1; [SCF SKP2b ]; Ren et al, 2008). The best-characterized CUL4 CRL from Arabidopsis acts together with DDB1, CONSTITUTIVELY PHOTOMORPHOGENIC1, DEETIOLATED1, and SUPRESSOR-OF-phyA-1051 to promote the degradation of the transcription factor ELONGATED HYPOCOT-YL5 (HY5) that normally represses hypocotyl elongation in light-grown Arabidopsis seedlings (Osterlund et al, 2000;Yanagawa et al, 2004;Chen et al, 2006Chen et al, , 2010.…”
mentioning
confidence: 99%